La relación con el saber astronómico tras el Gran Eclipse de América del Norte 2024 - Cardona, Giovanni; Cordero, Silvina; Leite, Cristina (Góndola, enseñanza y aprendizaje de las ciencias, 2026)
This article presents the results of a research study aimed at characterizing the relationship with astronomical knowledge formed by Physics and Physics Education students at a university in Bogotá, following their observation of the solar eclipse visible in North America on April 8, 2024, known as the Great North American Eclipse. Two students participated in the observation under different conditions: the Physics student traveled to Dallas, Texas, while the Physics Education student observed the eclipse from Guadalajara, Mexico. Afterward, they were asked to respond to a series of questions and complete a Knowledge Balance exercise. The data analysis identified key categories, which were then interpreted through the framework of the relationship with knowledge, based on the dimensions proposed by Bernard Charlot (identity-related, social, and epistemic). The relationship with astronomical knowledge is seen as a dynamic process involving continuous interactions with oneself, others, and the world, where understanding concepts and phenomena requires blending everyday observational experiences with the theoretical models learned in the classroom, moving beyond the static information found in textbooks and media. Additionally, the study advocates for the promotion of projects that foster astronomical observation in educational settings, such as tracking solar eclipses, where students record images and analyze astronomical parameters. In both cases, the students moved from merely defining the eclipse to actively experiencing it, enriching their identity, social, and epistemic connection to astronomical knowledge.